Characteristics of Japanese patients with pustulotic arthro‐osteitis associated with palmoplantar pustulosis: a multicenter study. (26th January 2020) - Yamamoto, Toshiyuki; Hiraiwa, Tomoko; Tobita, Rie; Hirano, Hirofumi; Masuda‐Kuroki, Kana; Ishii, Madoka; Murakami, Masamoto; Terui, Tadashi; Okubo, Yukari
Abstract: Background: Pustulotic arthro‐osteitis (PAO) is a major comorbidity of palmoplantar pustulosis (PPP), which is frequently seen in Japanese patients. To determine the characteristics of Japanese patients with PAO, we conducted a multicenter, retrospective epidemiologic survey at four university hospitals. Methods: Clinical features including age, gender, duration of disease, extrapalmoplantar lesion, smoking habit, focal infection, site of joint pain, bone scintigraphy with Technetium 99, and therapies were retrospectively evaluated. Results: In total, 165 patients with PAO were identified among 576 patients with PPP (28.6%). The male to female ratio was 1 : 3.7, and the mean age was 50.2 years. The mean disease duration of PAO was 6.0 years. Smoking habit was observed in 104 patients. Focal infection was detected in 74 patients, who developed tonsillar infection ( n = 41), sinusitis (8), odontogenic infection (40), and others (2). Fifteen patients had multifocal infection. Technetium bone scintigraphy was performed in 97 cases. Increased uptake was most frequently observed in the sternocostoclavicular regions, followed by wrist and ankle, sacroiliac joint, knee and elbow, finger and toe, lumbar spine, thoracic spine, scapula, and thigh. Patients were mainly treated with nonsteroidal anti‐inflammatory drugs, methotrexate, cyclosporine, antibiotics, and biologics, as well as tonsillectomy and dental treatment. Conclusion: PAO frequently involves the anterior chest wall of middle‐aged women with smoking habit and is closely associated with focal infection.